Study of Electricity Generation in Basic Sanitation Systems in Teófilo Otoni/MG (International Journal of Geoscience, Engineering and Technology, 2025)
The aim of this study was to evaluate the implementation of different sources of energy generation in the facilities of the basic sanitation service companies that serve the municipality of Teófilo Otoni, Minas Gerais. It is, therefore, the water supply collection system and the sanitary sewage treatment system. The systems are operated by Companhia de Saneamento de Minas Gerais (COPASA). The energy potential was calculated based on the power and energy equations and was taken into account the quantity of each resource. In the water collection system, the volume of water collected for supply was considered; in the sewage treatment plant, the volume of sewage treated was considered. For each energy potential, the total value was multiplied by the corresponding energy price in the last auctions in which each source participated. In view of the estimated revenue, a financial balance was made concerning energy costs in the water supply and sewage system. Finally, it was found that the financial savings would be positive in the short term if the generation projects were implemented, which could reduce the fees and tariffs applied to sanitation systems.
Keywords: Water collection; Sewage treatment; Renewable energy